The differential localization of a methyl group confers a different anti-breast cancer activity to two triterpenes present in olives. Issue 1 (20th November 2014) - Sánchez-Quesada, Cristina; López-Biedma, Alicia; Gaforio, José J.
Abstract : Uvaol (UV) and erythrodiol (ER) are two triterpenic dialcohols present in the minor fraction of virgin olive oil, in leaves and in the skin and drupe of olives. Abstract : Uvaol (UV) and erythrodiol (ER) are two triterpenic dialcohols present in the minor fraction of virgin olive oil, in leaves and in the drupe of olives. These triterpenes possess the same chemical structure and differ only in the location of a methyl group. It has been reported that they have antitumoral effects in leukemic cells, in skin mice tumours and, finally, in astrocytoma cells, but there are no evidences about their effects in highly invasive human breast cancer cells and human epithelial breast cells. For this purpose, we have evaluated their cytotoxic activities as well as their effects on cell proliferation, cell cycle profile, apoptotic induction, oxidative stress and DNA oxidative damage in both highly invasive human breast cancer cells (MDA-MB-231) and human epithelial breast cells (MCF10A). UV and ER showed different effects in normal and breast cancer cells, whereas both compounds possess the same structure, except for the location of a methyl group. UV protects from damage to DNA in both cell lines, whereas ER enhances damage to DNA in these cell lines. Thus, ER promotes apoptosis and arrests cell cycle in human epithelial breast cells. Hence, both compounds differ in their action in human breast cells apparently by the different location of only a methyl group.